Case Analysis of Forced Seizure of Fiduciary Collateral Due to Non-Performing Loan Financing (Case Study of Decision Number 36/Pdt.G.S/2023/PN Pdg) - Seselia Ongso (Jurnal Indonesia Sosial Sains, 2025)
Financial institutions are entities that aim to provide financial facilities to the public whose basic purpose is to raise funds and channel them into loans or credit, because financial institutions need legal certainty, then the Fiduciary Guarantee is present. This study aims to determine the legal protection obtained by debtors and creditors in the forced takeover of Fiduciary Guarantee Objects for bad credit financing and to understand the judge's consideration in realizing legal protection and justice in Decision Number 36/Pdt.G.S/2023/PN Pdg. The research method used in this research uses normative legal research methods which are studied using primary, secondary, and tertiary legal materials. The results of the research and analysis obtained in the first study are that the agreement made by the debtor and creditor will create an obligation that must be fulfilled. If one of the parties is unable to fulfill it, it will be declared a default. The definition of default has been explained in 1243 KUHPer and is again discussed in the Fiduciary Guarantee Law. However, in the Law there is a vague understanding of default and the power of execution of the Fiduciary Guarantee Object. Because, the Fiduciary Guarantee Object can only be executed if there is an act of default and the act must be contained in the agreement. Thus, if the Fiduciary Guarantee Object is executed without explaining the understanding of default and executorial power in the agreement, then the execution will be classified as an act of forced takeover. The second research result is that PT Maybank is prosecuted and punished for the forced takeover of the Fiduciary Guarantee Object and unlawful acts against the Guarantee Object belonging to Yurneli Darti and Dwiki Maulana due to bad credit financing. Where, the consideration of the Panel of Judges is based on the Constitutional Court Decision Number 18 / PUU-XVII / 2019 which indirectly weakens the creditor's right to execute the Fiduciary Guarantee Object.